The electrochemical properties of four dental casting suprastructure alloys coupled with titanium implants - Suleyman Hakan Tuna (Journal of Applied Oral Science, 2009)
OBJECTIVES: As the choice of suprastructure alloy to be combined with titanium for the oral cavity is still a much debated issue, the aim of this study was to investigate the electrochemical interaction of the suprastructure/implant couples under the determined experiment conditions. MATERIAL AND METHODS: The potentiodynamic polarization curves and open-circuit potentials (OCP) of four UCLA type suprastructures coupled with straight Swiss Plus implant fixtures were taken in Afnor type artificial saliva solution at 37°C. The concentration of ions leached into artificial saliva solutions was estimated with ICP-MS. SEM images of the margins of suprastructure/implant couples were obtained before and after the electrochemical tests. RESULTS: The OCP value of titanium became passive at the most negative potential. The lowest difference between the initial and constant OCP value was exhibited by the Au based suprastructure. Suprastructures made greater contributions to the potentiodynamic polarization curves of the implant/suprastructure couples. According to the ICP-MS results, Pd based and Au based couples dissolved less than Co-Ni based and Co-Cr based couples. CONCLUSIONS: Within the conditions this study, it may be concluded that the titanium implant forms a stable passive oxide layer in artificial saliva exposed to open air and does not affect the corrosion properties of the suprastructures. Pd based and Au based couples have been found to be more corrosion-resistant than base alloy couples.